A fair distribution of refugees in the European Union. Issue 3 (1st September 2016) - Holtug, Nils
ABSTRACT: In light of the large recent inflow of refugees to the EU and the Commission's efforts to relocate them, I raise the question of what a fair distribution of refugees between EU countries would look like. More specifically, I consider what concerns such a distributive scheme should be sensitive to. First, I put forward some arguments for why states are obligated to admit refugees and outline how I believe the EU should respond to the refugee crisis. This involves, among other things, resettling a proportion of refugees from countries neighbouring Syria in the EU. Second, I consider how the intake into the EU should be distributed between member states, that is, the shares different countries can be expected to admit. I discuss the relevance of a number of different factors that may be claimed to affect such shares, including population size, GDP, number of refugees admitted so far, unemployment rate, country-specific costs and cultural 'closeness'. Third, I consider whether the distributive scheme should be restricted to reflect specific states' responsibility for creating refugees in the first place, levels of racism and xenophobia, and whether other states are required to pick up the slack if some refuse to admit their fair share.